The Relationship Between Leader-Member Exchange Differentiation and Team Performance : Cooperative Communication as Mediatorhe Relationship Between Leader-Member Exchange Differentiation and Team Performance: Cooperative Communication as Mediator. (Global Business Management Review (GBMR), 2022)
The objective of this paper is to propose a conceptual model that explains the psychological process of how leader-member exchange (LMX) differentiation influences team performance. Based on theories of LMX and social information processing, it is argued that several important mechanisms underpin the relationship between LMX differentiation and team performance. Therefore, the researchers suggest that the team process mechanism such as cooperative communication serves as a psychological process to influence LMX differentiation and team performance relationship. The conceptual significance and how it affects the relationship is discussed in this paper. The proposed model increases the understanding of the role of cooperative communication in the relationship between LMX differentiation and team performance. The findings of this study will also help minimize the negative effect of LMX differentiation, and may ultimately lead to better team performance.